Aflatoxin M1 Contamination in Dairy Milk in Kathmandu, Nepal - Sujan Kafle; Madhav Paudel; Chanda Shrestha; Khadak Bahadur Kathayat; Ram Chandra Sapkota; Ananda Tiwari; Deepak Subedi (Toxins, 2024)
Aflatoxins (AFs), secondary metabolites produced by fungi, pose significant health risks, especially to children and elderly individuals. In developing countries such as Nepal, the tropical climate promotes fungal growth, leading to elevated levels of AF in animal feed and milk. In this study, we aimed to investigate the occurrence of aflatoxin M1 (AFM1) in dairy milk from the Kathmandu District and to assess husbandry practices contributing to contamination. We collected 84 milk samples, including raw milk from farms, retailers’ milk, and packet milk, and analyzed them using the competitive enzyme-linked immunosorbent assay (c-ELISA) technique. We also interviewed farmers to gather information on feeding and storage practices. All the collected milk samples were contaminated with AFM1, with 97.6% of the samples exceeding the European Union (EU) maximum permissible limit of 50 ppt (0.05 μg/kg). The majority (98.5%) of the farms included paddy straw, and all farms (100%) included concentrate in their feed regimens. Only half (52%) of the farms had proper storage facilities. Straw was mostly stored in sacks outdoors or left open in a shed, while concentrates were stored in a closed room or shed. This study reveals very high levels of AFM1 contamination in the milk samples, presenting a serious public health issue, and recommends comprehensive surveillance and further investigations across the country, especially given the limited research and literature available.